2021
DOI: 10.1108/jhr-11-2020-0548
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms related to air pollution, mask-wearing and associated factors: a cross-sectional study among OPD pollution clinic patients in Bangkok, Thailand

Abstract: PurposeThe purpose of this article was to investigate the relationship between symptoms related to air pollution, mask-wearing, mask choices and related factors.Design/methodology/approachA cross-sectional study among outpatient department (OPD) pollution clinic patients at Nopparat Rajathanee Hospital (PCNRH) during 2019 in Bangkok, Thailand.FindingsThe most common symptom after exposure to air pollution that affects treatment in the OPD is respiratory symptoms. A total of 45.7% (107/234) of the population we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our results suggest that older adults should pay more attention to protective measures against air pollution. Wearing protective masks and staying indoors are two effective methods [ 62 64 ]. However, some studies have found opposite results, indicating that younger people are more affected by air pollution [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that older adults should pay more attention to protective measures against air pollution. Wearing protective masks and staying indoors are two effective methods [ 62 64 ]. However, some studies have found opposite results, indicating that younger people are more affected by air pollution [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The N95 respirator mask protects against a range of particulate matter, such as dust, fumes, aerosols, smoke, pollen, mould spores, bacteria, and viruses (CDPH, 2022). Research has shown that wearing an N95 can help lessen respiratory symptoms (Tultrairatana & Phansuea, 2021). Not all N95 respirators meet international standards for effectiveness and safety.…”
Section: N95 Respiratorsmentioning
confidence: 99%
“…Epidemiological evidence has been provided for the human respiratory system [13][14][15]. Due to their size [16,17], short-term and long-term exposures [18,19] of ambient PM 2.5 cause more adverse health effects and toxicity than PM 10 [20][21][22]. Ambient PM 2.5 can easily move through the human body inhalation pathway.…”
Section: Introductionmentioning
confidence: 99%